Use of Digital Assessments how to Utilize Digital Bloom to Accommodate Online Learning and Assessments? - Husain, Farhat N. (Asian Journal of Education and Training, 2021)
As there has always been a concern regarding creation of reliable online assessments by educators, this academic article provides an idea for creating of online assignments for the inexperienced assessment literate teachers. This proposed model will show how to utilize Bloom’s model to create digital online assignments using ICT tools. The inspiration of this proposed model is taken from a combination of Benjamin Bloom’s Taxonomy and Andrew Churches Digital Bloom’s Taxonomy, as both focuses on the teaching and learning environment. Due to the pandemic 2020 approximate estimation of 87% of world’s student’s population (McGee, 2013; UNESCO, 2020) faced the issue of school closure, which gave a rise to online teaching, learning. Therefore, this paper examines the need of creation of reliable assessments which caters to the different students’ abilities. By this proposed model and with the Integration of Information and Communication Technology with Benjamin Bloom’s Cognitive Domain, this article will add a new dimension towards the online assessment. The main objective of this article is to utilize the common language and the terminology from the Blooms taxonomy for assessing the students depending on their needs and abilities to achieve the targeted learning outcomes.